An examination of major works for wind band, brass ensemble, and chamber winds: “Three songs from Sussex” by Hugh M. Stuart, “Fanfare for brass and percussion” by Karel Husa, and “Serenade no. 10 in B flat” by Wolfgang Amadeus Mozart - Johnson, Christopher Scott (Kansas State University, 2015)
This report provides a comprehensive research and teaching guide for three works for wind ensemble, brass ensemble, and chamber winds: Three Songs from Sussex by Hugh M. Stuart, Fanfare for Brass and Percussion by Karel Husa, and Serenade No. 10 in Bb, Largo, Allegro molto by Wolfgang Amadeus Mozart. Each chapter provides information on the composer, composition, historical perspective, technical considerations, stylistic considerations, musical elements, form and structure, other listening suggestions, and seating arrangement considerations. Also included are the lesson plan outlines that were used to teach each work, and a detailed score analysis grid. The report documents the full process of selecting, researching, rehearsing, and performing the selected literature with the hope that it will aid in future performances of the works.
Keywords: Analysis; Unit study; Hugh M. Stuart; Karel Husa; Wolfgang Amadeus MozartConducting; Music (0413)